Oxford handbook of medical statistics - Peacock, Janet (Janet L.); Peacock, Philip J. (Oxford : Oxford University Press, 2020)
This new edition of the'Oxford Handbook of Medical Statistics' provides doctors and medical students with a clear and concise explanation of statistical methods. It is an accessible and thorough account of a complex subject, and the previous edition has been described by readers as a'statistical Bible'.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 19, 2020).
Keywords: Medical statistics -- Handbooks, manuals, etc; Medicine -- Research -- Statistical methods -- Handbooks, manuals, etc